Experimental evaluations of elementary science programs: A best‐evidence synthesis. Issue 7 (29th April 2014) - Slavin, Robert E.; Lake, Cynthia; Hanley, Pam; Thurston, Allen
Abstract This article presents a systematic review of research on the achievement outcomes of all types of approaches to teaching science in elementary schools. Study inclusion criteria included use of randomized or matched control groups, a study duration of at least 4 weeks, and use of achievement measures independent of the experimental treatment. A total of 23 studies met these criteria. Among studies evaluating inquiry‐based teaching approaches, programs that used science kits did not show positive outcomes on science achievement measures (weighted ES = +0.02 in 7 studies), but inquiry‐based programs that emphasized professional development but not kits did show positive outcomes (weighted ES = +0.36 in 10 studies). Technological approaches integrating video and computer resources with teaching and cooperative learning showed positive outcomes in a few small, matched studies (ES = +0.42 in 6 studies). The review concludes that science teaching methods focused on enhancing teachers' classroom instruction throughout the year, such as cooperative learning and science‐reading integration, as well as approaches that give teachers technology tools to enhance instruction, have significant potential to improve science learning. © 2014 Wiley Periodicals, Inc. J Res Sci Teach 51:870–901, 2014.